For any positive a and n, it seems this inequality holds

$$ \sum\limits_{t=n+1}^\infty e^{-at} \leq \frac{1}{a}e^{-an} $$

How can I prove this inequality and does this holds for negative a ?

  • $\begingroup$ For $a > 0$ you can compute the left-hand side explicitly (using the geometric series formula). $\endgroup$ – Martin R Aug 16 at 11:06

If $a \le 0$, the left-hand sum doesn't converge.

If $a > 0$, then your inequality is true. Using the geometric series formula, we have $$\sum_{t=n+1}^{\infty}e^{-at} = \frac{e^{-a(n+1)}}{1- e^{-a}} = e^{-an} \frac{e^{-a}}{1-e^{-a}}.$$

This less than or equal to $\frac{1}{a}e^{-an}$, since $ \frac{e^{-a}}{1-e^{-a}}\le \frac{1}{a}$. To see this, recall that $a \le \frac{1 - e^{-a}}{e^{-a}} = e^a - 1$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.